Brachiocephalic atherosclerosis in patients with posterior circulation ischemic stroke - A. Yu. Vishnyakova; A. B. Berdalin; D. A. Golovin; S. Ed. Lelyuk; V. G. Lelyuk (Кардиоваскулярная терапия и профилактика)
Aim. To study echographic and acoustic characteristics of atherosclerotic plaques (ASP) in brachiocephalic arteries (BCA) in patients with acute posterior circulation ischemic stroke (PCIS).Material and methods. In this study we included data of duplex ultrasound from 235 patients (men, 129; women, 106; age, 59±12 and 63±10 years, respectively) with PCIS. Pathogenesis of PCIS was established only in 23 cases: in 17 (74%) — atherothrombosis, in 3 (13%) — cardioembolism, in 3 (13%) — lacunar stroke. Atrial fibrillation was established in 18,5% of patients. A total of 903 asymptomatic individuals were included in the control group, comparable with studied patients by sex and age.Results. The prevalence of ASP in vertebral arteries (VA) was equal in both groups. Also, no significant differences in the degree of VA stenosis were observed. Atherosclerotic lesions of common (CCA) and internal carotid arteries (ICA) on both sides were more often observed in control group, but the degree of their stenosis was higher in PSIS group (р<0,003). In ischemic stroke, stenosis of the right ICA was 47±17%, left ICA — 46±18%, while in asymptomatic individuals, right ICA stenosis was 40±14%, left ICA — 39±15%. In patients with PCIS, ASPs were significantly more often regarded as concentric (22,0% vs 10,4% in PCIS and asymptomatic individuals, respectively), prolonged (24,2% vs 7,5%), homogeneous (41,0% vs 21,1%), as well as were more likely to have an uneven contour (27,7% vs 2,8%).Conclusion. In patients with acute PCIS, the peculiarities of BCA atherosclerosis were recorded, distinguishing it from that in the asymptomatic population.